The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0037-86822011005000039
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment and lipid profile in HIV-infected children and adolescents treated with highly active antiretroviral therapy

Abstract: Introduction: HIV-infected children and adolescents treated with highly active antiretroviral therapy (HAART) regimens that include a protease inhibitor (PI) can show significant improvements in clinical outcomes, nutritional status and quality of life. The study aimed to report nutritional and metabolic alterations for pediatric patients continuously exposed to HAART and for healthy controls for up to 1 year. Methods: Clinical, anthropometric, lipid profile and food intake data were collected prospectively ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
1
13
1
Order By: Relevance
“…The differences seen for stunting prevalence and body fat percentage according to HAART regimens might be correlated and derived from growth deviations. However, it is important to point out that some authors have not considered bioelectrical impedance analysis a good parameter for assessing body fat abnormalities in the paediatric population (7,9) . Contri et al (7) evaluated patients aged 3-17 years under HAART and found that both groups (receiving and not receiving PI therapy) had similar and unchanged body composition.…”
Section: ‡Whomentioning
confidence: 99%
See 2 more Smart Citations
“…The differences seen for stunting prevalence and body fat percentage according to HAART regimens might be correlated and derived from growth deviations. However, it is important to point out that some authors have not considered bioelectrical impedance analysis a good parameter for assessing body fat abnormalities in the paediatric population (7,9) . Contri et al (7) evaluated patients aged 3-17 years under HAART and found that both groups (receiving and not receiving PI therapy) had similar and unchanged body composition.…”
Section: ‡Whomentioning
confidence: 99%
“…Despite the fact that bioelectrical impedance analysis has been used to assess body composition in HIVinfected children, it is difficult to analyse the results due to the lack of standards for children. Besides that, bioelectrical impedance analysis measures only whole-body fat and lean body mass, which does not allow the identification of body fat distribution abnormalities (9) . It is important to emphasize that alterations associated with antiretroviral therapy are likely a result of complex interactions between HIV infection, specific antiretroviral agents, age, gender, as well as host genetic and lifestyle factors (30) .…”
Section: ‡Whomentioning
confidence: 99%
See 1 more Smart Citation
“…1 Nutritional deficiencies are common among people with HIV, including HIV-infected youth. [2][3][4][5][6][7][8] In HIV-infected adults, nutritional deficiencies have been shown to affect immune status, disease progression, and mortality. [7][8][9][10][11][12][13][14][15] With the advent of highly-active antiretroviral therapy (HAART), concerns over nutritional deficiencies in the HIVinfected population have shifted from AIDS wasting syndrome, growth stunting, and chronic diarrhea to newly described long-term complications associated with chronic HIV infection secondary to increased inflammation, oxidative stress, and immune activation.…”
Section: Introductionmentioning
confidence: 99%
“…30,35,36 To date, however, few studies have investigated nutritional intake in relation to population recommendations among HIV-infected youth in developed countries, despite the serious implications for HIV disease progression and complication development in this population. 2,6,17,29,[36][37][38] And, notably, the few studies that have investigated this important topic used less stringent methods than what is recommended for nutrient intake assessment and/or only explored a few specific micronutrients.…”
Section: Introductionmentioning
confidence: 99%